Response of the Chinese Soft-Shelled Turtle to Acute Heat Stress: Insights From the Systematic Antioxidant Defense - Zhang, Wenyi; Chen, Bojian; Niu, Cuijuan; Yuan, Lin; Jia, Hui; Storey, Kenneth B. (Frontiers in Physiology, 2019)
Understanding the responses of animals to acute heat stress can help to reveal and predict the effect of more frequent extreme hot weather episodes on animal populations and ecosystems in the content of global climate change. Antioxidant defenses can help to protect animals against oxidative stress caused by intense temperature variation. In the present study, systematic antioxidant responses to acute heat stress (∆15oC and maintained for 12 h) and subsequent recovery were assessed by evaluating gene transcript levels and relative enzyme activities in tissues of Pelodiscus sinensis, a subtropical freshwater turtle. Targets included the upstream transcription factor nuclear factor erythroid 2-related factor 2 (Nrf2), antioxidant enzymes, and the glutathione (GSH) and ascorbic acid (AA) systems. Results showed three main patterns of expression change among antioxidant genes: (1) expression of Mn-superoxide dismutase (Mn-SOD), glutathione peroxidase 4 (GPx 4) and catalase (CAT) increased in response to heat stress or recovery in the liver; (2) transcripts of most genes did not change in brain, liver and kidney of P. sinensis; (3) expression of several GST isoforms were affected by heat stress or recovery in brain and kidney. However, relative enzyme activities involved in antioxidant defense were little affected by acute heat stress and recovery, indicating a relatively conservative antioxidant response in P. sinensis. Furthermore, results for malondialdehyde (MDA) levels indicated that acute heat stress and recovery did not lead to oxidative damage in turtle tissues and, in particular, MDA levels in spleen decreased along with increased splenic ascorbic acid concentration. Overall, the present study revealed a novel and conservative antioxidant response in P. sinensis, which may benefit high basal stress tolerance and relate with adaptation to climate change in freshwater turtles.